Three Principles of Transient Nucleate Boiling to be Used for Designing Super Strong Bainite - Kobasko, N. I. (European Journal of Applied Sciences, 2025)
The three principles of transient nucleate boiling are considered which are successfully used for recipes development and software designing. These principles were formulated based on accurate experiments of French, modified law of Fourier and many accurate experiments of the author of the current paper. Based on modified law of Fourier and existence of a double electrical boundary layer, it is stated that film boiling during quenching in cold electrolytes is completely absent and the main modes are transient nucleate boiling and convection. In many cases engineers use average heat transfer coefficient (HTC) for both nucleate boiling and convection that works perfectly when convective HTC is comparable with HTC of nucleate boiling process. But such approach generates big errors in cooling rate and time calculations when HTCs during boiling and convection differ many times between each other. The problem is solved easily when using the third principle to calculate core temperature at the end of nucleate boiling. In this case, core temperature is initial temperature for convection and the problem is solved. This approach is discussed in the paper to be used for recipes development and appropriate software design.